Digter as Danser/ Danser as Digter - Botha, Aniel (Department of English Language and Literature, 2014)
This dissertation provides an investigation into the similarities between poetry and ballet in relation to historical development, generating forces behind the artistic process, technical aspects, subject and theme, as well as the role of the mentor and the mentee in the creative effort. Works of Cleanth Brooks en Robert Penn Warren (Understanding poetry), Ruth Padel (The poem and the journey), Camille Paglia (Break, blow, burn), Jay Parini (Why poetry matters), Ottone M. Riccio (The intimate art of writing poetry) and other writers provide a theoretical basis upon which parallels between poetry and ballet are constructed. Practical examples from the collection Pirouette (Botha 2009), the works of several other poets and the ballet world serve to illustrate that poetry can be regarded as ""a dance with words"", whilst ballet can be viewed as ""poetry in motion"".